The Effect of The Problem Based Learning Model on Students' Cognitive Learning Outcomes in The Social Subject of Class VII MTSN 3 Pesisir Selatan - Amanda, Amanda; Sri Rahayu; Wibi Wijaya (JURNAL PENDIDIKAN IPS, 2025)
Student-centered learning models are believed to deepen understanding and increase student engagement in learning activities. To support this, the government developed the Independent Curriculum, which provides cues to teachers in delivering material and encourages the use of various learning strategies. This study aims to examine the effect of the implementation of Problem-Based Learning (PBL) on the cognitive learning outcomes of seventh-grade students in social studies at MTsN 3 Pesisir Selatan, and to assess the extent to which PBL can increase student participation during the learning process. This quantitative research used an experimental method and purposive sampling technique. Data were obtained through observation and tests, then analyzed using normality, homogeneity, hypothesis testing, and N-Gain tests. The results showed that the PBL model had a significant effect on students' cognitive achievement. The Mann-Whitney U test showed a significant difference between the experimental and control classes, with a significance level of <0.001. The N-Gain analysis showed an increase in learning outcomes of 22% in the experimental class (categorized as quite effective) and only 6% in the control class (categorized as ineffective). These findings indicate that PBL is an innovative learning alternative that is feasible to implement, especially in social studies.